2013
DOI: 10.1186/1746-1596-8-88
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of the growth factor progranulin is related with development of systemic lupus erythematosus

Abstract: BackgroundThis study is to investigate the expression of progranulin (PGRN) in systemic lupus erythematosus (SLE) patients and the effect of glucocorticoid (GC) treatment on its expression.MethodsThirty newly diagnosed severe SLE patients and 30 healthy subjects were enrolled in this study. The serum levels of PGRN and the inflammatory factors of SLE were detected by ELISA and the mRNA expression of these proteins were detected by real-time PCR.ResultsThe serum levels of PGRN, IL-6, PR3, TNFR, TNF-α and anti-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Glucocorticoid binds to cytoplasmic glucocorticoid receptors and forms receptor-corticosteroid complex, which translocates to the nucleus and regulates the transcription of target genes [ 36 ]. The present study found that glucocorticoid can affect the serum levels of both pro-inflammatory and anti-inflammatory cytokines, which accords with our previous studies [ 15 , 27 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Glucocorticoid binds to cytoplasmic glucocorticoid receptors and forms receptor-corticosteroid complex, which translocates to the nucleus and regulates the transcription of target genes [ 36 ]. The present study found that glucocorticoid can affect the serum levels of both pro-inflammatory and anti-inflammatory cytokines, which accords with our previous studies [ 15 , 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…The imbalance of immune system potentially results in the development of autoimmune disorders. It has been reported that multiple cytokines including pro-inflammatory such as IL-6 and IFN-γ [ 15 ] and anti-inflammatory cytokines such as IL-10 [ 26 ] and progranulin protein (PGRN) [ 27 ] and multiple immunocytes such as Treg [ 28 ], Th17 [ 29 ] and B cell [ 30 ] contribute to the pathogenesis of SLE. Our present study finds that apoE is elevated in active SLE patients accompanying the increase of IFN-γ, IL-6 and IL-10 and strongly correlated with IFN-γ, IL-6 and IL-10 serum levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed a significant difference between the 3 groups with respect to PGRN and IGFBP-2, except for ILGFBP-2, where no significant difference was noted between the CKD and control groups. These findings agreed with the findings of some studies on PGRN [14,34]. Tanaka et al [13] also found higher levels of PGRN in SLE patients than in controls.…”
Section: Discussionsupporting
confidence: 89%
“…PGRN associates with some members in the TNF receptor superfamily, including TNFR1, TNFR2 and DR3 [12] , [14] [16] , and possesses the ability to suppress inflammation in various kinds of conditions [12] , [17] – [23] . The association between PGRN levels and systemic inflammation and autoimmunity has been reported [24] [28] , for instance, serum levels of PGRN were elevated in systemic lupus erythematosus and related with disease activity [25] . Auto-antibodies against PGRN have also been found in several autoimmune diseases, including rheumatoid arthritis, psoriatic arthritis, and inflammatory bowel disease, and such antibodies promoted a proinflammatory environment in a subgroup of patients [29] [31] .…”
Section: Introductionmentioning
confidence: 98%